Bentuk dan Isi Mantra - Edi Suwatno (Humaniora, 2004)
Mantra (magic formula) is a speech that invites an inscrutable power to heal, to expel ghost, ask rain, deliver accident, etc. Based on poetic principles, mantra is structured from words order element such as poetry like rhyme, song; that is considered as elements of inscrutable power spoken by dukun or pawang to protect from other inscrutable power. Mantra manifests to various things/ways. It could be poetry, pantun (traditional poetry), kidung, song, or lyrics, and lyric prose. Mantra also has various content or functions such as healing diseases, raising seedlings of rice plant, postponing rainm, etc.